PENGGUNAAN MEDIA BUKU CERITA BERGAMBAR DALAM MENUMBUHKAN LITERASI ANAK USIA DINI SAAT PANDEMI - Hanifa Hafiza; Nurniswah; M. Fauzi (Alzam: Journal of Islamic Early Childhood Education, 2023)
Children's literacy or reading and writing abilities during the pandemic are very worrying. Developing early childhood literacy can encourage their language skills. One way to encourage literacy growth is by using picture story books. Picture story books are one of the media most liked by children. So that picture story books can foster students' reading literacy.The aim of writing a conceptual article is to increase insight into the application of picture storybook media in fostering early childhood literacy during the pandemic.The application of picture story book media is carried out through the collaboration of teachers and parents who become figures for the children, and what is conveyed by the teacher will be obeyed and followed by the children. To convey picture storybook media during the pandemic, teachers used two methods, namely the question and answer method and the storytelling method, and conveyed stories with various expressions. Meanwhile, parents foster literacy in early childhood at home through picture story books, such as reading fairy tales before bed.